ABSTRACT ART IN GREECE: THE PIONEER ARCHITECTS - Sarakatsianou, Vasiliki (Design/Arts/Culture, 2022)
The early years of the 20th century is a period of deep intellectual reappraisal as well as social and intellectual change. The modern painters’ experiments have come right to the forefront of artistic attention. Modernism was the point when the idea of radical and innovating arts, the experimental, technical, aesthetic idea reached a formal crisis, leading to abstract art. Modernism predicates the origins of post-war art as Post-Modernism adds to the abundance of versions of Modernism. After World War II abstract expressionism achieved international influence. On the contrary, in Greece during the first half of the 20th century, abstract art was absent. It actually appeared in the 1950s but it became dominant in the 1960s. In the post-war period, there were many talented Greek architects such as, Marthas, Xenakis, Proveleggios, Tsingos, Fatouros who became interested in painting, following the contemporary art tendencies. This paper focuses on abstract painting in Greece both in the early years of the 20th century as well as in the 1950s and 1960s. In this context, the contribution of Greek architects as pioneer visual artists in the 1950s and 1960s to the gradual establishment of abstract painting in Greece is probed, using as a methodological tool mainly artworks and written sources of that period. It is argued that Greek architects with their artworks and their wide range of activities in the field of visual arts express the modern consciousness and pave the way for abstract art in Greece.